Factors of Change in Bureaucrat's Work Climate and Behavior of Post-Pandemic Public Services - Mulyaningsih, Mulyaningsih (Budapest International Research and Critics Institute-Journal (BIRCI-Journal), 2021)
A pandemic is a global disease outbreak, just like the COVID-19 pandemic that has hit the whole world. At the stage where the pandemic has begun to decline, bureaucrats as the front line of public services need to prepare everything related to their duties considering that during a pandemic emergency there are still shortcomings in public services and open opportunities for national economic recovery to move again. Post-pandemic requires a change in the work climate in organizational culture, bureaucratic behavior and the effectiveness of public service management to welcome economic recovery in a new, more dynamic order. The method in this research is descriptive qualitative (Sugiyono, 2015) analyzing and describing phenomena or research objects through social activities, attitudes and perceptions of people individually or in groups using a literature study. The research is described on changes in the work climate of bureaucrats and the behavior of bureaucrats towards public services after the pandemic. The results show that the management transformation and bureaucratic climate refer to the ideal model of governance, namely dynamic governance and diversity governance, with its strategic pillars covering several aspects, namely bureaucratic management, institutional and organizational business processes, performance accountability and supervision, public services, and the use of information and communication technology (ICT) within the scope of an electronic-based government system and remains on the path of public service standards. To create superior post-pandemic bureaucrats according to the plan to formulate bureaucratic management in the era of the new normal order that emphasizes more on the digital system, changing the planning system, procuring bureaucrats by building digital government, having information technology literacy, strengthening competencies according to organizational development. And transforming the employee development system through online, internship, or hands-on learning into the workplace. The post-pandemic bureaucracy must be adaptive to these changes so that bureaucratic reform can really be realized in its implementation in the field as a public service.